2015
DOI: 10.14260/jemds/2015/567
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Intravenous Versus Rectal Acetaminophen After Adeno Tonsillectomy in Children

Abstract: INTRODUCTION: Doses of acetaminophen 15mg/ kg intravenous and 40 mg/kg rectally produce similar effect-site concentrations. However, the clinical effectiveness of these routes has not been compared. The aim of this study was to compare the efficacy of analgesia (in terms of duration of analgesia and effect on pain intensity) in children following adenotonsillectomy after acetaminophen either 15 mg/ kg IV or 40 mg/ kg rectally. METHODS: Fifty children, aged between 5 and 14 yrs., undergoing elective adenotonsil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Mostly, studies conducted are on children due to better acceptability of rectal route versus parenteral or IV route. [ 5 6 9 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly, studies conducted are on children due to better acceptability of rectal route versus parenteral or IV route. [ 5 6 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…in 2015 concluded that time to first rescue analgesia was significantly longer in children receiving rectal acetaminophen (8.96 ± 3.46 h) compared with those receiving IV acetaminophen (6.00 ± 1.63 h). [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with a study by Beltramini et al ,[ 10 ] the therapeutic threshold for CHIPPS score was considered as 4 or more and for VAS was 4. [ 11 ]…”
Section: Methodsmentioning
confidence: 99%